Enhanced-AODV Routing Protocol to Improve Route Stability of MANETs - Abdullah, Ako; Ozen, Emre; Bayramoglu, Husnu (Zarka Private Univ, 2022)
Establishing and maintaining link stability in Mobile Ad hoc Networks (MANETs) is one of the key challenging issues. Topology changes in MANET because overhead traffic that leads to consuming extra energy of nodes as well as decreasing the performance of routing protocols. Thus, a comprise approach should be considered during the design of a routing scheme in MANETs to deal with challenges incurred by the mobility of the nodes. In this study, a simple efficient routing scheme called Enhanced_AODV (E-AODV) is proposed, aiming to enhance Ad Hoc On-Demand Distance Vector (AODV) routing protocol performance by constructing the most stable and reliable route from source to the destination node. In this routing scheme, the remaining lifetime of links and hop count are the metrics considered for calculating the Route Stability Factor (RSF) that can be utilized as a cost metric to establish the best route between source and destination node. The simulation results reveal that the proposed E-AODV routing scheme effectively outperforms the conventional AODV routing protocol and Stable and Bandwidth Aware Dynamic Routing Protocol (SBADR) in terms of packet delivery ratio, average network throughput, average end-to-end delay, and normalized routing overhead.
Keywords: MANET; routing protocol; shortest path; route stability; network density; MANET; routing protocol; shortest path; route stability; network density